Analysis Of Factors Affecting The Profitability In Consumer Goods Sector Companies Listed On The Indonesia Stock Exchange In 2015-2020 Period - Dwi Verasasti Tarihoran; Endri Endri (Publikasi Indonesia, 2021)
This study examines factors that affect profitability in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period. In this study, the population are consumer goods sector companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The technique used purposive sampling that obtained as many as 19 companies for the research objects. The independent variable in this study is Return On Assets (ROA). In contrast, the independent variables are Current ratio (CR), Debt to equity ratio (DER), Total Asset Turnover (TATO), Working Capital (WC), Sales Growth (Grow), Size Company (Firm Size), World Oil Price (Oil Price), and Exchange Rate. The test method to determine the effect of the independent variable on the dependent variable is the panel data regression analysis method which is processed using E-VIEWS 12. Based on the results of simultaneous research, it is known that CR, TATO, GROW have a significant positive effect on profitability (ROA), WC and FIRM Size has a negative and significant impact on profitability (ROA), while DER, Oil Price and Exchange Rate (Exchange) do not have a substantial effect on profitability (ROA).